Experimental research on consolidation creep characteristics and microstructure evolution of soft soil - Yuan, Jie; Gan, Yuexin; Chen, Jian; Tan, Songming; Zhao, Jitong (Frontiers in Materials, 2023)
The influence of creep deformation of soft soil on engineering construction can’t be ignored. In order to deeply understand the macroscopic mechanical properties and the evolution mechanism of soft soil in microscope during consolidation creep, one-dimensional consolidation creep tests and SEM tests of Nansha soft soil are carried out in this paper. Then the consolidation creep characteristics, microscopic parameters of particles and pores under different loading pressures are obtained by the Image J image processing. The results of experiment and image processing show that (1) The creep process of Nansha soft soil is divided into the initial instantaneous deformation phase, the attenuation creep phase and the stable creep phase. The creep deformation increases with the consolidation creep stress during the three phases. (2) During the creep process, the distance between particles decreases and some particles are gradually broken, the quantity of particles and pores increases but the volume of them decreases. At the same time, the shape of particles and pores changes from nearly round and strip to nearly oval. (3) The consolidation creep stress determines the particles distance and the degree of fragmentation. And this trend is more obvious with the increase of the consolidation creep stress.